Problem of National School in Conceptions of Latvian Teacher’s Professional Organizations (LSS and LNSS), 20th of 20th Century - Vugule, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The study outlines the problems of the “national school” concept formation in content of the “old school” (to 1918) conditions, and discusses how its understanding significant changes after the founding of the Latvian Republic, how this concept revealing in the new options of democracy and national self-determination. The study is looking for a meaning that included in the LSS concept of “national education” and LNSS concept of “education on the national - cultural grounds”. In Latvia from the 1918th to the 1934th the concept of "National school" in activities of lead teacher’s professional organizations (LSS and LNSS) are not developed in a holistic approach. Idea of “National school” in this time is active, it formed in a new discourse of integrated democratic nation – try to include all national minorities.